LITERATURE REVIEW : THE INFLUENCE OF SOCIAL MEDIA, WORD OF MOUTH AND PRICES ON PURCHASING INTENTIONS YAKULT IN BEKASI CITY - Ika Wijayanti (IJESM Indonesian Journal of Economics and Strategic Management, 2023)
This research focuses on deepening the role of socialmedia, word of mouth and price on interest in buyingyakults. This research is a literature review tostrengthen previous findings from relevant variables.This research uses a quantitative approach to answerthe research hypothesis. The population is not knownwith certainty but the unit of analysis in this researchis respondents who know and have used yakultproducts in the city of Bekasi. The SPSS statistical toolcan be used to test the suitability of the data and thevalidity of the research model. Hypothesis testinguses the t test and f test and determination.